Deciphering the “Doxycycline Deficiency Syndrome”: Defining the Characteristic Clinical, Laboratory and Imaging Findings in Patients Presenting with Leptospirosis, Q Fever and Rickettsial Diseases in Far North Queensland, Tropical Australia - Hayley Stratton; Callum Pownell; Megan Sandeman; Patrick Rosengren; Cody Price; Alexandra G. A. Stewart; Roderick Gavey; Toni Kinneally; Kathy Petoumenos; Simon Smith; Josh Hanson (Tropical Medicine and Infectious Disease, 2026)
Background: The “doxycycline deficiency syndrome” is a colloquial term used in tropical Australia to describe the overlapping, non-specific findings seen in leptospirosis, Q fever, and the rickettsial diseases scrub typhus and Queensland tick typhus (QTT). A laboratory confirmed diagnosis is frequently delayed, however, early differentiation of these potentially life-threatening infections has important implications for clinical management. Methods: We examined consecutive laboratory-confirmed cases of leptospirosis, Q fever, and rickettsial diseases managed at a referral centre in tropical Australia. The patients’ symptoms, clinical signs and simple laboratory and radiology investigations at presentation were compared. Results: There were 111 cases of leptospirosis, 59 cases of Q fever, and 34 cases of rickettsial disease (17 cases of QTT and 17 of scrub typhus). Patients with leptospirosis had a shorter duration of symptoms and were more likely to have gastrointestinal symptoms, arthralgia, haemoptysis, hypotension, conjunctival suffusion and abnormal chest auscultation at presentation than patients with the other infections. They were more likely to have renal impairment and an elevated creatine kinase but less likely to have an elevated serum ferritin and serum lactate dehydrogenase. Patients with leptospirosis were more likely to have alveolar and multilobar changes on chest imaging. Patients with Q fever were more likely to have abnormal liver function tests at presentation but were more likely to have preserved renal function and normal chest imaging. Patients with rickettsial disease were more likely to have a rash, an eschar, lymphadenopathy and splenomegaly. Overall, 76/204 (37%) required ICU admission, of whom 56 (74%) had leptospirosis, but all 204 patients survived to hospital discharge. Conclusions: Leptospirosis, Q fever, and rickettsial diseases can have a similar presentation, but simple clinical, laboratory and imaging findings can help distinguish these infections and expedite their optimal management.